EKONOMI PERTANIAN SEBAGAI SUATU SISTEM PEMBAGUNAN - Wahab Wahab (CV. ADIBA AISHA AMIRA, 2023)
Agricultural economics is an applied social science that deals with how producers, consumers and society use scarce natural resources in the activities of production, processing, marketing and consumption of agricultural products. The purpose of this study is to determine the relationship between the regional economy, both economic growth and development. This study uses a qualitative descriptive method with a literature study approach to provide an explanation of the relationship between the agricultural sector and the regional economy. The existence of the agricultural sector in economic development is still considered a passive sector and merely a supporting element as input for other sectors, especially the industrial sector as well as trade and services. However, this can also be an opportunity as well as a challenge for the agricultural sector to grow rapidly and increase its competitiveness. Even though the agricultural sector in an area is not a leading sector, it does not mean that the agricultural sector can be sidelined because it is cheated which is important in the process of economic growth and is closely related to food security, labor absorption, sources of industrial raw materials, and sources of community income which then have an impact on growth the economy of a region.